Relationship between self-concept, family relationship and externalizing behavior among adolescents in Selangor - Zakaria, Patonah; Md. Noor, Amna; Mohd Khir, Azlina (Secholian Publication, 2018)
The main purpose of this study is to determine the relationship between self-concept, family relationship quality and externalizing behavior problem (aggressive behavior and delinquency behavior) among adolescents in Selangor. Besides that, this study also to determine the level of self- concept, family relationship quality and externalizing behavior among secondary school students as well as to compare the differences between these three variables according to sex. A total of 400 students (nmale =53%, nfemale=47%) from secondary schools were selected in this study. The multi-stage cluster sampling technique was used during sample selection. Data were obtained from self- administered questionnaire that are consist of Individual Protective Factors Index Questionnaire (1992), Family Relationship Characteristics (1997), Aggression Scale (2001) and Problem Behavior Frequency Scale (1977). The findings revealed that majority of students have moderate level of self- concept, family relationship quality as well as externalizing behavior. In terms of sex differences, the results showed that family belief, family structure and externalizing behavior have significant differences according to sex (t= -4.393 to 7.588, p<0.01). Moreover, result indicated that there were negative significant relationship between self-concept, family cohesion and family structure with aggressive behavior (r= -0.210 to -0.153, p<0.01). Moreover, the result showed the negative significant relationship between family structure and delinquency behavior (r= -0.104, p<0.05). These results suggest that self concept and family relationship quality are an importance factors for the development of adolescents behaviors.